Collisional excitation in space: recent advances and future challenges in the JWST era - Tonolo, Francesca (Frontiers in Astronomy and Space Sciences, 2025)
This perspective offers a viewpoint on how the challenges of molecular scattering investigations of astrophysical interest have evolved in recent years. Computational progress has steadily expanded collisional databases and provided essential tools for modeling non-LTE astronomical regions. However, the observational leap enabled by the JWST and new observational facilities has revealed critical gaps in these databases. In this framework, two major frontiers emerge: the characterization of collisional processes involving heavy projectiles, and the treatment of ro-vibrational excitation. The significant computational effort of these investigations emphasizes the need to test and develop robust theoretical methods and approximations, capable of extending the census of collisional coefficients required for reliable astrophysical modeling. Recent developments in these directions are outlined, with particular attention to their application and their potential to broaden the coverage of molecular systems and physical environments.